XALQARO BAHOLASH DASTURLARIGA MOS TEST TOPSHIRIQLARINING BAJARILISHI HAQIDA AYRIM MULOHAZALAR - Shodiyev, Sh.Sh. (SCIENCE and SOCIETY, 2020)
This article examines the ability of schoolchildren to apply the acquired theoretical knowledge in everyday life. Some analytical data on the implementation of the international PISA assessment program for assessing the development of students' skills are presented.
Keywords: experiment; test levels; context; quantity; statistics